MENENTUKAN PREMI DAN RESIKO INDIVIDU UNTUK ASURANSI PERAWATAN JANGKA PANJANG - , TASNIM RAHMAT, S.Pd.I. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Long-term care (LTC) can be modeled by markov model multistate. Long-term care insurance is insurance that is quite difficult to determine the appropriate premiums and risk, for lack of information obtained. Moreover the duration of their lives is strongly influenced by demographic trends. The framework adopted is a multistate, continuous time models, the determination of premiums and individual risk.